Structural disorder and distinctive motifs in the C-terminal region of the MADS-domain transcription factors are conserved across diverse taxa - Erandi Ramírez-Aguirre; Teresa Beatriz Nava-Ramírez; Alejandra A. Covarrubias; Adriana Garay-Arroyo (PLoS ONE, 2025)
Plants have acquired the ability to adapt and respond to varying environmental conditions through modifications in their developmental programs. This adaptability relies on the plant’s capacity to sense environmental cues and respond via diverse signal transduction pathways and transcriptional regulation. Transcription factors are central in these processes, orchestrating specific gene expression in both developmental and stress responses. In Arabidopsis thaliana, 91% of transcription factors contain large intrinsically disordered regions (IDRs). The structural flexibility in these regions is critical in protein-protein interactions and contributes to functional versatility across different cell types. MADS-domain transcription factors constitute an eukaryotic protein family involved in a diversity of developmental processes and stress responses. Using bioinformatic tools, we found that most Arabidopsis MADS-domain proteins contain IDRs (≥30 residues) in their C-terminal region, with a higher proportion of global disorder in Type II compared to Type I MADS-domain proteins. Remarkably orthologous proteins from non-plant species in the Eukarya domain (Drosophila melanogaster, Saccharomyces cerevisiae, and Homo sapiens) also present disordered C-terminal regions, containing longer IDRs than those found in Arabidopsis, or other analyzed plant species. Additionally, conserved motifs were identified within the C-terminal IDRs of Arabidopsis Type I and Type II MADS-domain proteins, suggesting interactions with co-regulatory partners. We also identified putative activation domains in the C-terminal region of Type I and Type II MADS-domain proteins. The involvement of IDRs in selecting co-regulators is further supported by the identification of Molecular Recognition Features (MoRFs) in Type II MADS-domain proteins. The conserved structural disorder in the C-terminal region of MADS-domain proteins, which includes specific motifs, across diverse domains of life provides valuable insights into their structural properties and mechanisms of action as transcriptional regulators.